1992
DOI: 10.1021/bi00125a005
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipids: deuterium NMR study of the influence of ceramide fatty acid characteristics on the carbohydrate headgroup in phospholipid bilayers

Abstract: Galactosylceramides bearing a variety of different pure fatty acid chains were 2H labeled in the carbohydrate headgroup at C6 of the terminal galactose residue, for study by 2H NMR. Fatty acids investigated included the 24-carbon saturated lignoceric acid, 18-carbon saturated stearic acid, cis-9,10-unsaturated oleic acid, and D- and L-stereoisomers of alpha-hydroxystearic acid. Headgroup-deuterated glycolipids were incorporated at 10 mol % into unsonicated bilayers of 1-palmitoyl-2-oleoylphosphatidylcholine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 51 publications
7
20
0
Order By: Relevance
“…6A,B), similar to that described for bilayers in the fluid state (Singh et al 1992). Liposomes incubated in the presence of 10 mM of Mg 2÷ did not modify the size and the structure of their lipid bilayers (Fig.…”
Section: Freeze-fracture Electron Microscopysupporting
confidence: 82%
See 1 more Smart Citation
“…6A,B), similar to that described for bilayers in the fluid state (Singh et al 1992). Liposomes incubated in the presence of 10 mM of Mg 2÷ did not modify the size and the structure of their lipid bilayers (Fig.…”
Section: Freeze-fracture Electron Microscopysupporting
confidence: 82%
“…Then, liposomes were cooled down at 4°C during I h before freeze-fracture. An aliquot of these liposomes was sandwiched between a pair of Balzers (Nashua, NH) copper support plates and frozen in Freon 22 cooled in liquid nitrogen (Singh et al 1992). Glycerol at final concentration of 15% was added to prevent freeze damage of the lipid samples (Verkleij et al 1982;Gaillard et al 1991).…”
mentioning
confidence: 99%
“…This hypothesis is supported by the observation that HFAGalC and HFA-sulfatide form more stable calcium-dependent complexes than their nonhydroxylated counterparts (Menikh et al, 1997;Koshy et al, 1999). Biophysical studies on lipid monolayers showed that the phase behavior of ceramides is significantly affected by 2-hydoxylation (Singh et al, 1992). The galectin-4-dependent stabilization of so-called "super rafts," detergent-resistant membranes that are detergent insoluble at 37°C (Braccia et al, 2003), appears to depend on the specific binding of galectin-4 to the 2-hydroxylated isoforms of GalC and sulfatide (Delacour et al, 2005).…”
Section: Although Fa2hmentioning
confidence: 86%
“…These possibilities seem to be ruled out by previous data [29,30] indicating that the lipid chain length does not significantly affect the conformation of saccharide moiety. Moreover, it has been reported that in the case of galactosylceramide embedded in PC vesicles [lo], GAO preferentially affects the molecular species carrying longer lipid chains, their saccharide moiety being more exposed above the apolar-polar interface of the bilayer.…”
Section: Discussionmentioning
confidence: 86%